WARPFIELD 2.0: feedback-regulated minimum star formation efficiencies of giant molecular clouds - Rahner, Daniel; Pellegrini, Eric William; Glover, Simon; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. Star formation is an inefficient process and in general only a small fraction of the gas in a giant molecular cloud (GMC) is turned into stars. This
Advance access publication 2018 December 3
Gesehen am 19.08.2020